Stanlake's Introductory Economics - Stanlake, G.F. (George Frederick) 1919-; Grant, S.J. (Harlow, Essex, England : Pearson Education Limited, 2000)
Stanlake's Introductory Economics offers you an analytical approach to contemporary economic problems and a clear explanation of the principles underlaying current economic issues.
First published 1967.
ECONOMICS
Includes glossary pg. 637 - 641 and index pg. 642 - 646.
Keywords: Economics -- Problems, exercises, etc; Economics